EFFECTIVENESS OF USE OF COOPERATIVE LEARNING NUMBERED HEADS TOGETHER (NHT) LEARNING MODEL ON MATHEMATICS LEARNING OUTCOMES OF STUDENTS IN SMP N 1 SRANDAKAN - Erny Styaningsih; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2017)
The selection of learning models that are less precise can affect student learning success. Learning in SMP N 1 Srandakan is still centered on the teacher so students tend to be passive in class. This study aims to determine whether there are differences in students' mathematics learning outcomes by using the NHT type of cooperative learning models as well as knowing the effectiveness of the NHT type cooperative learning models for student mathematics learning outcomes. The design of this study is Subjects Posttest Only Control Group Design. The population in this study were students of class VIII of SMP N 1 Srandakan Regency of Bantul in the 2015/2015 academic year with a total of 190 students. Samples in this study were taken using a random sampling technique obtained by class VIII D as an experimental class and class VIII E as a control class. Data collection is done by the test method. Testing instruments using the test the validity of the different power tests and reliability tests. Data analysis techniques using analysis prerequisite tests include normality test with Chi-Square formula, homogeneity test with Bartlett test, and hypothesis testing with t-test. Based on calculations with a significant level α = 5% and degrees of freedom 62, it can be concluded that: (1) There are differences in mathematics learning outcomes between students who use the NHT type of cooperative learning models and students who use the direct learning model. This is indicated by the results of the first hypothesis test that = 2.3802 and = 1.99897, so > . (2) The NHT type of cooperative learning model is more effective than the direct learning model. This is shown from the results of the second hypothesis test that = 2.3802 and = 1.6698, so >